Carcinoembryonic antigen level of draining venous blood as a predictor of recurrence in colorectal cancer patient - Soo Young Lee; Kyung Sun Min; Jung Kee Chung; In Mok Jung; Young Joon Ahn; Ki-Tae Hwang; Hye Seong Ahn; Seung Chul Heo (Annals of surgical treatment and research, 2011)
We designed this study to evaluate the efficacy of carcinoembryonic antigen in draining venous blood (vCEA) as a predictor of recurrence. Methods: Draining venous and supplying arterial bloods were collected separately during the operation of 82 colorectal cancer patients without distant metastasis from September 2004 to December 2006. Carcinoembryonic antigen was measured and assessed for the efficacy as a prognostic factor of recurrence using receiver operating characteristic (ROC) and Kaplan-Meier curves. Results: vCEA is a statistically significant factor that predicts recurrence (P = 0.032) and the optimal cut-off value for vCEA from ROC curve is 8.0 ng/mL. The recurrence-free survival between patients with vCEA levels ＞8 ng/mL and ≤8 ng/mL significantly differed (P ＜ 0.001). The significance of vCEA as a predictor of recurrence gets higher when limited to patients without lymph node metastasis. The proper cut-off value for vCEA is 4.0 ng/mL if confined to patients without lymph node metastasis. The recurrence-free survival between the patients of vCEA levels ＞4 ng/mL and ≤4 ng/mL significantly differed (P ＜ 0.001). Multivariate analysis revealed vCEA is an independent prognostic factor in patients without lymph node metastasis. Conclusion: vCEA is an independent prognostic factor of recurrence in colorectal cancer patients especially in patients without lymph node metastases. KCI Citation Count: 5